Peran Pekerja Sosial Menjadi Konsuler Bagi Disabilitas - Angga trisnanto; Muhammad Iqbal; Rifki Awaludin; Ati Kusmawati (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Human Rights (HAM) are basically rights that every human being has and have the right to enjoy because human rights are rights inherent in humans and are the most basic rights and without exception. Likewise, people with disabilities have the same rights, obligations and position as humans in general. Social work is a helping profession that provides insight into other people through continuous verbal or non-verbal interaction with clients. This research uses a qualitative type with a single case study approach. This research aims to determine the role of social workers as consular officers for people with disabilities. This research shows that social workers in dealing with disabilities act as motivators, counselors, liaisons or informers, liaisons, advocates and facilitators.